Evaluation of Complementary Food Prepared from Sorghum, African Yam Bean (Sphenostylis stenocarpa) and Mango Mesocarp Flour Blends - Yusufu, P.A.; Egbunu, F.A.; Egwujeh, S.I.D.; Opega, G.L.; Adikwu, M.O. (Pakistan Journal of Nutrition, 2013)
The use of Sorghum, African yam bean (Sphenostylis Stenocarpa) and Mango mesocarp (Mangifera indica) flour blends in the formulation of complementary food was studied. Traditional Weaning Food (TWF) obtained from 100% sorghum was used as the control sample. The sorghum, African yam bean and mango mesocarp flour were blended in the ratio of 5:3:2 respectively and used to formulate complementary food (SAM). The sample of complementary foods produced were subjected to chemical, functional and sensory properties analyses. The result of the chemical composition showed a significant (p<0.05) increase in the protein and fat level of the formulated complementary food (8.9±1.09 to 17.4±1.19% and 1.5±0.11 to 3.50±0.31%, respectively. However, a significant p<0.65) decrease in the carbohydrate level (78±1.00 to 67.59±1.35) was observed vitamins A composition of formulated food was 3.54μg/mg. Functional properties evaluated showed no significant (p<0.05) difference in the bulk density but a high water absorption (70.6±3.3%), Emulsion (6.00±0.30%) capacities and reconstitution index (85±1.0%) were noticed. The sensory panelists rated the formulated complimentary food highly for taste, colour, flavour, texture and the overall acceptability. The formulated complementary food is a protein-rich product with good functional and sensory properties. Use of plant protein sources in local food formulations appeared to be vital in upgrading their nutritional, functional and sensory properties.